Induction of Specific Chromosomal Aberrations by Adenovirus Type 12 in Human Embryonic Kidney Cells - zur Hausen, Harald (1967)
Nonrandom chromosomal breaks in chromosomes 1 and 17 were provoked in human embryonic kidney cells 24 hr after infection with adenovirus type 12. These chromosomal changes disappeared in persistently infected cultures. Neutralization of the virus with type-specific antiviral serum prior to infection prevented the occurrence of chromosomal aberrations. No viral deoxyribonucleic acid (DNA) synthesis, as determined by autoradiography, was seen in metaphases containing adenovirus type 12-induced chromosomal aberrations. Ultraviolet irradiation of the virus reduced chromosomal aberrations linearly. This reduction in aberrations was fourfold slower than the inactivation of viral infectivity. At 24 hr after infection of cells with purified (3)H-labeled adenovirus type 12, the isotope was found to be associated with the nuclei. The uptake of isotope was reduced ninefold when the labeled virus was neutralized with type-specific antiviral serum. This difference is considered to account for neutralization of labeled virions. In metaphases infected with labeled viruses, most of the clustered grains were seen only on one arm of the chromatid, even after 72 hr. Isochromatid labeling was found, however, in a small percentage of chromosomes, and increased with time after infection. This increase was threefold between 24 and 72 hr after infection, whereas the mean grain counts decreased twofold during the same period. This has been tentatively interpreted to mean that most of the viral DNA molecules or parts thereof are merely attached to cellular chromatin, but a small fraction of them becomes gradually integrated as time proceeds. Certain chromosomal sites appeared to be preferentially labeled when chromosome 2 was used as a model for evaluation.